Influence Of Motivation On Employee Performance In BPJS Health Office Sumedang Branch - Ryan Kurniawan Feryana (Journal of Bussines Management Basic, 2023)
This research entitled effect of Motivation on Performance at the BPJS Kesehatan Branch Office Sumedang. As for the problems this research is lacking optimizing upgrade facilities employee performance. Research purposes this is to find out the motivation, employee performance, the magnitude of the influence motivation on employee performance in Branch Health BPJS Office Sumedang. This research using a method approach descriptive with analytical techniques quantitative, done through the method survey. Saturated sampling is used, so that the entire population is used as a research sample of 45 person. Research data using simple regression analysis, correlation test, coefficient of determination and hypothesis testing. The results of this study show that motivation is 2631 (good) with an average of (94%), performance employees of 2,962 (good) with average (93%), next the magnitude relationship between motivation and performance employees at the Health BPJS Office Sumedang branch of 0.994 (very strong relationship), and the effect of motivation on performanceemployees at the Health BPJS Office Sumedang branch of 0.988 or 98.8%, so that means a lot significant effect on motivation on employee performance in the Office Health BPJS Sumedang Branch and the remaining 2% is affected by other factors such as discipline on performance employees, such as attendance rate, obedience to work regulations, obedience on work standards, levels high vigilance, work ethically and leadership attitudes towards performance employees, such as self-awareness, treat others on an equal basis equality and have empathy that is not researched by researchers, so it can be concluded that motivation is very influential strong on employee performance in Branch Health BPJS Office Sumedang.